El Indice de la Ventaja Comparativa Revelada (VCR) entre el Perú y los principales exportadores del mundo: el caso de la Región Lambayeque - Heredia Pérez, Jorge (2009)
This paper presents and applies a conceptual framework to regional Competitiveness using the Index of revealed competitiveness introduced by Balassa in 1965 for the Lambayeque Region in the northern part of Peru with the end to determine the products more competitive of this region. In the first part of the article the competitiveness review is presented from the Porter approach to Systemic Competitiveness. The advantage of this method is to identify the competitiveness of the regional products and services as a function of the import and export values of the country in contrast with the same values of the other countries in the world. The FAOSTAT data is used for that purpose. The results shown that the crop most competitive are the avocados, the bananas, mangoes, asparagus, dry chilies and coffee. Nevertheless when these products are compare with others countries such as Chile and Brazil only mangoes and asparagus are strongly competitive. However both products are considered commodities rather than value added products and its competitiveness lies in comparative advantage such as clime and soil.